Process of soil salinization as a function of watermelon mineral fertilization - Costa, Manoel Fernandes da; Silva, Graciene de Souza; Albuquerque Junior, Eden Cavalcanti de; Araújo, Cícero Antônio de Sousa; Oliveira, Fabio Freire de; Tavares Filho, Gilberto Saraiva (Comunicata Scientiae, 2023)
The watermelon (Citrullus lanatus L.) is a cucurbitaceous plant of great social and economic importance in Brazil, especially in the north-eastern region. However, anthropic actions through the practice of irrigation, fertigation and fertilization in an inadequate way, have potentiated the salinization of the soil becoming this one of the main factors that limit the production and the quality of the fruits. In this work, the effects of the application of mineral fertilization on the salinization of soil cultivated with watermelon were evaluated. The experiment was performed in the city of Petrolina-PE, with four repetitions, using five treatments: (T0) no fertilization, (T1) NPK fertilization, (T2) average dose of NPK practiced by producers, (T3) maximum dose of NPK from producers having potassium chloride as a source of potassium and (T4) maximum dose of NPK from producers having potassium sulfate as a source of potassium, at two different depths: 0.00 - 0.20 m and 0.20 - 0.60 m. The soil chemical attributes analyzed were pH, electrical conductivity (EC), organic matter, phosphorus, potassium, sodium, calcium and magnesium. The increase in the continuous application of mineral fertilizers raised the electrical conductivity values of the soil to levels prejudicial to the crop.